FINANCIAL FRAUD, ECONOMIC OFFENCE IN INDIA: CRIME PREVENTION THROUGH HEURISTIC METHOD - GULPHAM, SHAHANSHAH (Innovare Journal of Social Sciences, 2022)
Financial inclusion is the decade’s big achievement of the Government of India through the opening zero balance saving accounts mass level in nationalized scheduled banks. In recent past, India is facing big challenges to tackle the white collar and economic crime problems responsible for ruining the entire economic management and system of public policy allocations. The present paper is analyzing the various publicly concerned financial fraud and multiple economic offenses which are directly or indirectly affecting the country’s economy and responsible for sea-merging the financial condition of the nation. Even, there are multiple preventive provisions implemented to prevent such offences by the government and various initiatives taken parallel to combat the economic crisis. In this paper, a heuristic method of crime prevention has been suggested to tackle similar offences and reduce the occurrence of the frauds.